PERAN NEGARA MELEMAHKAN HAK BURUH GARMEN DALAM RANTAI NILAI GLOBAL: STUDI KASUS PT GSS - Irwansyah Irwansyah; Ade Rahayu Aprilia (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
Some studies have studied that violations of the leading brands and subcontractor management cause the weakening of garment workers' rights in the Global Value Chain. Unfortunately, little research examines how local governments also play role in reducing the protection rights of garment workers of global value chain. This study aims to examine the resistance of PT GSS garment workers to their employers and the local government when demanding the enforcement of their labor rights. This research uses a qualitative method with a case study approach, collecting data through interviews and observation. A combination of employer and local government actions has developed a production regime at PT GSS, similar to a globally fragmented despotism concept. This research has found that companies weaken workers' resistance by forming counter-unions, target-chasing systems, management's intransigence, and unilateral vacation by the company. Meanwhile, the local governments facilitate despotism in the production regime by regulations that accommodate arbitrary layoffs, lowering the minimum wages, and lack of functioning of a supervisory function. The workers resisted this fragmented despotism with various kind of protest actions at the workplace and international campaigns.Beberapa penelitian telah mempelajari bahwa pelanggaran dari leading brand dan manajemen subkontraktor menyebabkan pelemahan hak-hak pekerja garmen dalam Global Value Chain. Sayangnya, sedikit penelitian yang meneliti bagaimana pemerintah daerah juga berperan dalam mengurangi hak perlindungan pekerja garmen dalam rantai nilai global. Penelitian ini bertujuan untuk mengkaji resistansi buruh garmen PT GSS terhadap manajemen dan pemerintah daerah ketika menuntut penegakan hak-hak pekerja. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus, pengumpulan data melalui wawancara dan observasi. Kombinasi tindakan pengusaha dan pemerintah daerah telah mengembangkan rezim produksi di PT GSS, serupa dengan konsep global fragmented despotism. Penelitian ini telah menemukan bahwa perusahaan melemahkan resistansi pekerja dengan membentuk serikat tandingan, sistem kejar target, dan watak keras manajemen. Sementara itu, pemerintah daerah memfasilitasi despotisme dalam rezim produksi dengan peraturan yang mengakomodasi PHK sepihak, menurunkan upah minimum, dan kurang berjalannya fungsi pengawasan. Para buruh melawan despotisme yang terfragmentasi ini dengan berbagai aksi protes di tempat kerja dan kampanye internasional.